Economies of scale in local government services: a meta analysis / Siew King Ting, Rene Villano and Brian Dollery - Ting, Siew King; Villano, Rene; Dollery, Brian (Universiti Teknologi MARA Cawangan Sarawak, 2018)
In this paper, a meta-regression analysis is presented by 38 empirical studies on the size of scale in various local government services. Our results show that income classification was the most important factor in determining size of scale and all selected local government services recorded decreasing size of scale in the recent decades, with water services exhibiting the largest decreasing size of scale. The existence of scale effects has important ramifications for local government structural reform, given the globally indifferent results of local government reorganization